Chemoprotection of amazonian Mauritia flexuosa fruit pulp against ammonia and nitrite toxicity to postlarvae shrimps Litopenaeus vannamei - Cleber dos Santos Simião; Grecica Mariana Colombo Mariana Colombo; Robson Matheus Marreiro Gomes; Patrícia Baptista Ramos; Marcelo Borges Tesser; Wilson Wasielesky Junior; José María Monserrat (Boletim do Instituto de Pesca)
The chemoprotection of "buritiââ‚¬Â Mauritia flexuosa (inclusion in diet: 0-control group; 1.25; 2.50; 5.00; and 10.00% W/W) to Litopenaeus vannamei postlarvae (PL) exposed to ammonia or nitrite was investigated. Analyzed variables include antioxidant (ACAP) and oxidative damage (TBARS) responses and levels of total carotenoids. The results indicated that there was no significant difference (p >0.05) in zootechnical variables between diets. The PL carotenoid content (R2 = 0.86), ACAP (R2 = 0.78), and TBARS (R2 = 0.91) showed a dose-dependent relationship with the inclusion levels of "buritiââ‚¬Â (p <0.05). After 43 days, juvenile shrimps were exposed for 96 h to ammonia (0.48 mg NH3-N L-1) or nitrite (40 mg NO3 L-1). Higher scavenging activity against peroxyl radicals was observed in PL fed with 2.50 and 5.00% of "buritiââ‚¬Â (ammonia exposure), or 5.00 and 10.00% (nitrite exposure) of "buritiââ‚¬Â inclusion. Content of reduced glutathione was higher in shrimps exposed to ammonia and fed with 10.00% of "buritiââ‚¬Â. Lipid peroxidation levels were lower in shrimps exposed to ammonia or nitrite and previously fed with inclusion higher than 2.50% of "buritiââ‚¬Â. The increased scavenging activity and lower lipid peroxidation in ammonia or nitrite-exposed organisms and previously supplemented with "buritiââ‚¬Â point to a hormetic response that increases the resilience of L. vannamei to cope with nitrogenous compounds, pointing to the use of this fruit as a chemoprotectant agent.